Mortgage valuation: a quasi-closed-form solution - Viegas, Cristina (2022)
The substantial growth observed in commercial mortgage contracts during the last two decades justifies a greater academic effort in order to develop adequate valuation models. In the vast majority of cases, the literature in this field has presented only numeric solutions. In order to obtain these numeric solutions, highly complex calculation techniques are required, which make the process overly slow and expensive. The main objective of this work is to make a contribution in a hitherto underexplored area of financial research: the development of a contingent claims commercial mortgage valuation model with a closed-form solution. The model developed in the present paper constitutes one of the first attempts to identify closed-form solutions for commercial mortgage valuation. It is also a valid alternative to models proposed up to now in the specific field of commercial mortgage valuation